CaMn0.5Ir0.5O2.5: An anion-deficient perovskite oxide containing Ir3+ - Page, J; Hayward, M (American Chemical Society, 2019)
Reaction between CaMn0.5Ir0.5O3 and NaH, either through solid-solid contact or via a gas mediated reaction process, yields the topochemically reduced phase CaMn0.5Ir0.5O2.5 in which Mn3+ and Ir3+ cations are located within a partially anion-vacancy disordered lattice. Magnetization data from CaMn0.5Ir0.5O2.5 can be fit by the Curie–Weiss law to yield C = 1.586 cm3 K mol–1 and θ = −86.9 K, consistent with a combination of S = 2, Mn3+ and S = 0, Ir3+. On cooling below T ∼ 110 K, the system undergoes a transition to a spin-glass state, consistent with the observed Mn/Ir cation disorder and frustration between Mn-O-Mn and Mn-O-Ir-O-Mn magnetic couplings. The degree of reduction and the observed anion-vacancy disorder are discussed on the basis of the d-orbital filling of the transition-metal cations.